Features in the vertical structure of the meridional flow field over the continental rise east of Abaco, the Bahamas - Aazani, Mujahid; Kanzow, T.; Bryden, H. L. (European Geosciences Union, 2007)
Since Spring 2004, the RAPID-MOC mooring array (Monitoring the Atlantic Meridional Overturning Circulation at 26.5N) and the MOCHA array (Meridional Overturning Circulation and Heat-flux Array), have been a system continuously monitoring the Atlantic Meridional Circulation (MOC) in the subtropical North Atlantic. Using two year long current meter records (2004-2006), along with historical data (1986 – 1997), as decribed by Lee et.al. (1990) and Lee et.al. (1996) of the western boundary moorings, we analyze the vertical structure of the complex flow field in the Antilles Current (AC)/ Deep Western Boundary Current (DWBC) regime